In the shadow garden eaudiobook - Parker, Liz (2022)
The richly atmospheric and luminous debut about three generations of women whose magic is as much a part of life as love, death, and the rich, dark earth beneath their feet—perfect for fans of Practical Magic and Midnight at the Blackbird Cafe. There's something magical about Yarrow, Kentucky. The three empathic witches of the Haywood family are known for their shadow garden—from strawberries that taste like chocolate to cherry tomatoes imbued with the flavors of basil and oregano. Their magic can cure any heartache, and the fruits of their garden bring a special quality to the local bourbon distillery. On one day every year, a shot of Bonner bourbon will make your worst memory disappear. But the Haywoods will never forget the Bonners' bitter betrayal. Twenty years ago, the town gave up more than one memory; they forgot an entire summer. One person died. One person disappeared. And no one has any recollection of either. As events from that fateful summer start to come to light, there must be a reckoning between the rival Haywood and Bonner families. But untangling the deep roots of this town's terrible secrets will expose more than they could ever imagine about love, treachery, and the true nature of their power.